Optimal Staffing Policy and Telemedicine - TARAKCI, H. (Institutional Knowledge at Singapore Management University, 2007)
We study the optimal strategy of a specialty hospital in providing traditional face-to-face consultations via experts and remote medical services via tele-specialists. We model the whole system as a queuing problem and provide the optimal staffing policy for this hospital by taking into account the various cost components, such as those for staffing, incorrect treatment, and waiting. We also find the optimal investment in telemedicine technology that offers the best trade-off between the quality and accuracy of telemedicine services and the cost of technology. Under certain conditions, the hospital does not offer any telemedicine services. When it does, it may or may not invest in the most advanced technology available. Finally, we provide the optimal tele-specialist policy of which patients to treat remotely via telemedicine and which patients to refer to the experts for a face-to-face consultation. We show that a policy of treating all patients via tele-medicine is never optimal.